Porcine circovirus‐like virus P1 in cattle, goats and rabbits in China. Issue 1 (21st September 2017) - Wen, L.; Mao, A.; Fan, Z.; Li, W.; Xiao, Q.; Liu, Q.; Xie, J.; He, K.
Summary: Porcine circovirus‐like virus P1, a novel single‐stranded circular DNA virus, is a potential causative agent of post‐weaning multisystemic wasting syndrome in swine. In this study, we detected P1 strains in serum samples from cattle, goats and rabbits suffering different clinical symptoms, in Jiangsu Province, China. We sequenced the whole genomes of six P1 strains, which showed 99.4%–100% nucleotide sequence similarity and were closely related to other porcine‐origin P1 isolates. The sequences of six non‐porcine‐origin P1 viruses were most closely phylogenetically related to other porcine‐origin P1 sequences. Therefore, the P1 virus has a wide host range in China.